Thermodynamic analysis of a High Temperature Pumped Thermal Electricity Storage (HT-PTES) integrated with a parallel organic Rankine cycle (ORC) - Chen, Long Xiang; Hu, Peng; Zhao, Pan Pan; Xie, Mei Na; Wang, Feng Xiang (Energy conversion and management, 2018)
•A high temperature PTES (HT-PTES) is proposed based on an electric heater.•The energy storage density of HT-PTES is more than twice that of PTES.•When combined with ORC the performance of HT-PTES improved significantly.•A novel parallel ORC is proposed to recover the heat at high temperature.•HT-PTES combined with parallel ORC is the most promising system in five types of storage systems. Pumped thermal electricity storage (PTES) using packed bed is an attractive large-scale energy storage technology. The performance of conventional PTES is limited by the existing technology of compressor, such as low isentropic efficiency and cannot bear high temperature. In this work, a high temperature PTES (HT-PTES) based on an additional electric heater is proposed to enhance the energy storage capacity of PTES. Waste heat, which produced due to the irreversibility of heating, compression and expansion process of both PTES and HT-PTES, is recovered by the organic Rankine cycle (ORC) to generate power. Air and argon (Ar) are investigated as working fluid for PTES and air is selected due to its high thermal performance and economy. Five types of PTES combined with ORC system namely, PTES, HT-PTES, PTES + ORC, HT-PTES + ORC and HT-PTES + parallel ORC are investigated based on transient analysis method. The simulation results show that combined with ORC is an effective approach to improve the round trip efficiency (RTE) of both PTES and HT-PTES. In the five types of combined systems, the HT-PTES + parallel ORC is considered as a more promising large-scale energy storage technology which advantages can be illustrated as follows: (1) it with an acceptable RTE of 47.67%, which is 5.68% higher that of HT-CAES and is only 2.46% lower than the maximum RTE of the five types; (2) it shows an appropriate operating pressure, which are 1.05 MPa for HT-PTES subsystem and 12.20 MPa for ORC subsystem (significantly lower than that of 31.2 MPa for ORC in the HT-PTES + ORC); (3) it presents a considerable energy storage density of 218.69 MJ/m3, which is more than twice that of PTES + ORC (88.14 MJ/m3).